Volume 3: 17th International Conference on Advanced Vehicle Technologies; 12th International Conference on Design Education; 8t 2015
DOI: 10.1115/detc2015-47805
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of Automotive Aerodynamics Using DrivAer Model

Abstract: The use of experimental and numerical investigation to predict the aerodynamic characteristics of road vehicles is a standard practice in automotive design and development. Fundamental research has been often conducted on generic models with limited applicability to realistic cars. The DrivAer model developed in TU München possesses more representative car features. To encourage the use of the DrivAer model in independent research work, the experimental results and some numerical results were published. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…From this perspective, these results suggest the front-mounted sting design adopted does not markedly affect the performance near the moving ground, similar to the top and side supports typically used for these applications. 3,4,9,11 Impact on mean turbulence production within the wake. The contours of mean turbulent kinetic energy (K) presented in Figure 8 provide differences in turbulence production within T2.…”
Section: Time-independent Wake Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…From this perspective, these results suggest the front-mounted sting design adopted does not markedly affect the performance near the moving ground, similar to the top and side supports typically used for these applications. 3,4,9,11 Impact on mean turbulence production within the wake. The contours of mean turbulent kinetic energy (K) presented in Figure 8 provide differences in turbulence production within T2.…”
Section: Time-independent Wake Characteristicsmentioning
confidence: 99%
“…This technique also facilitates moving ground use and wheel rotation, and has been shown to be less detrimental to drag measurements. 3,8 Miao et al 4 reported drag coefficient increases limited to 2% on a notchback passenger car model with both fixed and moving ground use. For the hatchback configuration on a stationary ground, drag increased by 1.4%, with results using a moving ground found only marginally more significant (1.7%).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations